ETIKA SEORANG ENGINEERING DALAM PROYEK KONSTRUKSI DESAIN AND BUILD - Manurung, Edison Hatoguan; Hutagaol, Kerlima; Muzaqi, Ganang (SINERGI : Jurnal Riset Ilmiah, 2025)
The Design and Build method is a modern approach to construction project implementation that integrates the planning and implementation processes within a single work contract. In this system, an engineer plays a crucial role, serving as a technical designer, quality controller, and strategic decision-maker. This study aims to identify and analyze the primary role of an engineer in a Design and Build project, as well as to understand the challenges and competencies required to carry out these responsibilities. The research method used was descriptive qualitative, using literature review, observation, and interviews with professional engineers in the field. The results indicate that engineers act as a liaison between project owners, planners, and implementers, and have a significant responsibility for ensuring structural safety, cost efficiency, and project sustainability. Furthermore, integrity and professional ethics are key factors in technical decision-making. With the right competencies and early involve